Analysis for Improvement of Doppler Tomography Imaging of Objects Scattering Continuous Ultrasonic Waves - ŚWIETLIK, Tomasz; OPIELINSKI, Krzysztof J. (Archives of Acoustics, 2020)
The paper describes an innovative ultrasound imaging method called Doppler Tomography (DT), otherwise known as Continuous Wave Ultrasonic Tomography (CWUT). Thanks to this method, it is possible to image the tissue cross-section in vivo using a simple two-transducer ultrasonic probe and using the Doppler effect. It should be noted that DT significantly differs from the conventional ultrasound Doppler method of measuring blood flow velocity. The main difference is that when measuring blood flow, we receive information with an image of the velocity distribution in a given blood vessel (Nowicki, 1995), while DT allows us to obtain a cross-sectional image of stationary tissue structure. In the conventional method, the probe remains stationary, while in the DT method, the probe moves and the examined tissue remains stationary. This paper presents a method of image reconstruction using the DT method. First, the basic principle of correlation of generated Doppler frequencies with the location of inclusions from which they originate is explained. Then the exact process and algorithm in this method are presented. Finally, the impact of several key parameters on imaging quality is examined. As a result, the conclusions of the research allow to improve the image reconstruction process using the DT method.